The relationship between inflation rate with stock prices of property, industrial products and finance sector at Bursa Malaysia (KLSE) / Noorfazdila Hamzah (Faculty of Business and Management, 2007)
This study is conducted to answer the question whether there is a relationship between inflation rates with stock prices of property, industrial products and finance (counters) sector at Bursa Malaysia (KLSE). The data collected on monthly basis for ten years from January 1997 to December 2006. Here inflation rate is considered as dependent variable and property, industrial products and finance stock price are considered as independent variables. On this study, the sample of 20 counters for each sector was used and as a result, 8 counters in property sector which are APH, DRLM, DR, DJC, ENOP, BOL, PR and PTGTIN has a positive relationship with inflation. While, AM, PJDEV, ASAS, BRD, DD, EKR, GPH, KRBN, NEGARA, OIB, PAR and PRIME shows a negative relationship with inflation. Moreover, 11 counters in industrial products sector which are ACB, AJY, ALC, AMAL, ANC, ESSO, CBEE, CIM, DRBHCOM, DOLM and IRCB shows a positive relationship with inflation. ACP, AJR, ASM, CCM, CGB, HEX, GBH, MIG and SINDORA have a negative relationship with inflation. Furthermore, 10 counters in finance sector which are BIMB, CMS, HDBS, HLBANK, INSAS, JER, KLCITY, MBSB, PBBANK and RHB has a positive relationship with inflation. While, AHB, AMM, APX, BCAP, COMMERZ, EON, KAF, KNK, LPI and MAY shows a negative relationship with inflation.